A antropologia na tradição alemã (Blumenberg, Gehlen, Plessner…) - Feron, Olivier (Trabalhos de Antropologia e Etnologia, 2020)
The author gives a brief introduction to the German anthropological thought from the philosophical anthropology point of view, focusing mainly in the nineteenth and twentieth centuries. The aim is to identify briefly the problems and some of the debates which define the philosophical field radically opened for the first time by Immanuel Kant.